Pengaruh Pemberian (CMA) dan Pupuk Mutiara Terhadap Pertumbuhan Dan Produksi Kacang Panjang (Vigna Sinensis L.) - Hia, Kasi Mirus; Samah, Eri; Linda Br Jabat, Yelfi Yana (JURNAL AGROPLASMA, 2025)
This study aimed to evaluate the effect of Arbuscular Mycorrhizal Fungi (AMF) and Mutiara fertilizer on the growth and production of yardlong bean (Vigna sinensis L.). The research was conducted at the experimental field of Universitas Pembinaan Masyarakat Indonesia using a randomized block design with two factors: AMF doses (0, 5, 10, and 15 g/plant) and balanced NPK Mutiara fertilizer (0, 5, 10, and 15 g/plant). Parameters observed included plant length at 14, 21, 28, and 43 days after planting (DAP). Statistical analysis revealed that neither AMF nor Mutiara fertilizer, individually or in combination, significantly affected plant length during any observation period. However, a growth trend was observed, with the highest combination dose (15 g AMF + 15 g Mutiara) producing the tallest plant length of 3090 cm at 43 DAP. These findings suggest a potential synergistic effect between biofertilizers and chemical fertilizers in supporting plant growth, though not statistically significant. Further research with greater replication and more sensitive experimental design is recommended to validate these preliminary findings. Keywords: agrotechnology, balanced fertilization, long bean, mutiara fertilizer, mycorrhizal fungi